IMPROVING THE STUDENTS’ SPEAKING PERFORMANCE THROUGH THE IMPLEMENTATION OF TIERED ACTIVITIES - Pradana Akbar Tanjung; Fitri Hidayati; Andyani Larasati (UAD TEFL International Conference)
This study aims at implementing differentiated instruction in the form of tiered activities to the students of Government Study Program, Faculty of Social and Political Studies, Yogyakarta Muhammadiyah University. There are three objectives in this study; 1) to give contribution in improving students’ speaking performance and to solve the problems that the students have in terms of their readiness in the selected Free Conversation class, 2) to provide new activities which can be used as a consideration to evaluate the current material provided by the institution, 3) to provide related language instructors new insight and experience in applying a certain kind of approach, that is the use of differentiated instruction through tiered activities. 19 students from Class IP A2 who were taking the Free Conversation class were the participants of this study. The study was started by conducting observation, pre-test, and need analysis. Then, it was followed by the implementation and post-test. To measure the success of this study, pre-test and post-test scores were compared. The result indicated that the implementation of the tiered activities in Free Conversation class helped to improve the students’ speaking performance.